Detection of group B rotavirus in fecal specimens by dot hybridization with a cloned cDNA probe. - Eiden, J J (1989)
Cloned cDNA copies were synthesized from the genomic RNA of the IDIR strain of group B rotavirus (GBR) isolated in Baltimore, Md. These clones were screened for hybridization with heterologous GBR to identify cDNA for use in dot hybridization experiments. In multiple screening experiments, cDNA clones derived from gene segment 3 provided the most intense hybridization signals. 32P-labeled probes were produced from one of the gene 3 clones, and these were employed in dot hybridization assays. Purified preparations of bovine GBR were detected in concentrations of greater than or equal to 0.5 ng, and GBR was detected in fecal specimens obtained from five of six infected calves. Four of six human fecal specimens containing the Baltimore strain of GBR were also positive in the hybridization assay, while GBR was identified in only one of the six specimens by means of immunoelectron microscopy. A fecal specimen obtained from a patient infected with the adult diarrhea rotavirus strain of GBR was also positive in the dot hybridization assay. Fecal specimens from uninfected humans, calves, and rats, as well as specimens containing group A rotaviruses, did not hybridize with the cloned cDNA probe.